2021
DOI: 10.1007/s00371-021-02252-w
|View full text |Cite
|
Sign up to set email alerts
|

A history of crowd simulation: the past, evolution, and new perspectives

Abstract: This paper aims to discuss the past, evolution, and new perspectives in crowd simulation. Many work have been produced and published in this area that was launched approximately 30 years ago. In this paper, we re-visited the main aspects of the area, presenting the periods and evolution we had in the past. In addition, we also discuss the present and possible trends for the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 109 publications
0
9
0
Order By: Relevance
“…The area of group perception has grown in recent years. Group perception is essential for learning about group patterns [McDonnell et al 2008, Molina et al 2021, Musse et al 2021]. However, these results did not take into account the effect of UV and the use of VR in these scenarios, which is what we want to explore in our work.…”
Section: Related Workmentioning
confidence: 97%
See 1 more Smart Citation
“…The area of group perception has grown in recent years. Group perception is essential for learning about group patterns [McDonnell et al 2008, Molina et al 2021, Musse et al 2021]. However, these results did not take into account the effect of UV and the use of VR in these scenarios, which is what we want to explore in our work.…”
Section: Related Workmentioning
confidence: 97%
“…The authors performed perceptual experiments, which explored how different anomalies have relative importance. Regarding the interactivity of experiments with VR [Schwind et al 2018, Pelechano and Allbecky 2016, Musse et al 2021, in the work of [Seymour et al 2017] the authors observed the effect of UV theory on user interaction with the photo-realistic human avatar without just looking at its appearance. The area of group perception has grown in recent years.…”
Section: Related Workmentioning
confidence: 99%
“…The models showed that different behavioral processes could lead to similar aggregate outcomes, such as consensus and polarization. Building on these models by including more psychological variables and incorporating more detailed simulations could result in a useful method to predict future mass behaviors (Musse et al, 2021).…”
Section: Figurementioning
confidence: 99%
“…Crowd simulation has been widely studied in the field of computer graphics, where each agent carries out tasks in a dynamic environment with complex interaction among multiple moving or static agents. 1 One important capability of crowd simulation is the accurate state prediction of each agent in the near future through a series of decision cycles. Here the agent can be considered as an individual pedestrian, a moving car, a mobile robot and even an obstacle.…”
Section: Introductionmentioning
confidence: 99%
“…The blue one is generated by our model through adding the Gaussian kernel term. The length of the solid line is1 2 |u| .…”
mentioning
confidence: 99%